A CLINICAL PROFILE OF MALAYSIAN PRE-SCHOOL CHILDREN WITH TYPE 1 DIABETES: OBSERVATIONS FROM A SINGLE CENTRE - Mavinkurve, Meenal; Jalaludin, Muhammad Yazid; Leong, Annie; Noordin, Mazidah; Samingan, Nurshadia; Zaini, Azriyanti Anuar (Journal of the ASEAN Federation of Endocrine Societies, 2021)
INTRODUCTION Type 1 diabetes (T1DM) is the most common form of childhood diabetes in Malaysian children, the median age being 7.6 years. Worldwide, younger children are increasingly being diagnosed with T1DM, especially in the under 5’s age group. Vague clinical symptoms may lead to a protracted presentation and increase the risk of severe complications. This study aims to report the clinical characteristics of Malaysian pre-school (<7 years) children with T1DM . METHODOLOGY A retrospective review of the demographic and clinical data on children < 7 years of age diagnosed with T1DM at the University of Malaya Medical Centre between January 1st 2010-Dec 31st 2019 was conducted. www.asean-endocrinejournal.org 2021 MEMS Annual Congress 64 www.asean-endocrinejournal.org Poster Abstracts (Adult | Paediatric) RESULTS There were 119 diagnoses of TIDM during the study period. Forty-percent (n=47) were pre-schoolers, mean age being 4.16 ± 1.85 years. Boys comprised 60% (n=28) and the Chinese ethnicity was predominant, 32% (n=15). DKA occurred in 79% (n=37) at presentation, of these 73% (n=27) were moderate-severe DKA. The mean Hba1c was 11.98 ± 1.95% and 80% (n=38) were positive for atleast 1 pancreatic antibody, GAD-65 70% (n=33) being the most frequent. PICU admission occurred in 47% (n=22) cases and the mean length of stay was 7.8 ± 2.7 days. The lowest rate of pre-school T1DM was seen in 2011, 20% (1/5 cases), and the highest in 2017, 63% (12/19 cases). Within the pre-schooler group, 43% (n=20) were misdiagnosed, respiratory infections being the most common 60% (n=12) misdiagnosis. Furthermore, 90% (n=18) in the misdiagnosed group presented in DKA, of which 35% (n=12) were severe. CONCLUSION T1DM is the most common form of childhood diabetes in Malaysia. Pre-school children <7 years of age with T1DM are often misdiagnosed, present in moderate-severe DKA and require PICU admission. Future multi-centre studies need to evaluate the risk factors contributing to these findings and the long-term outcomes in pre-schoolers with T1DM